2017
DOI: 10.1055/s-0043-111375
|View full text |Cite
|
Sign up to set email alerts
|

Does Sporadic Amyotrophic Lateral Sclerosis Spread via Axonal Connectivities?

Abstract: IntroductionAmyotrophic lateral sclerosis (ALS) is characterized by rapid progressive paralysis of the striated skeletal musculature [1,2]. The present review focuses on sporadic disease (sALS), which constitutes the majority of cases without a known genetic mutation. Clinically similar but inherited (familial) forms that display very diverse pathologies [3][4][5][6][7] are not taken into account here.The pathological process underlying sALS entails abnormal changes of an endogenous and predominantly intranucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…A multicentre study of eight contributing centers with 253 ALS patients and 189 healthy controls ( Müller et al, 2016 ) confirmed the most significant alterations to be localized in the CST (corresponding to stage 1) and found additional significant WM tract changes in the frontal lobe, the brainstem, and hippocampal regions (corresponding to stages 2–4). The localization of these DTI-based in vivo results were in accordance with the definition of the post-mortem neuropathological stages ( Brettschneider et al, 2013 ; Braak et al, 2017 ).…”
Section: In Vivo Transfer Of the Staging Conceptsupporting
confidence: 77%
“…A multicentre study of eight contributing centers with 253 ALS patients and 189 healthy controls ( Müller et al, 2016 ) confirmed the most significant alterations to be localized in the CST (corresponding to stage 1) and found additional significant WM tract changes in the frontal lobe, the brainstem, and hippocampal regions (corresponding to stages 2–4). The localization of these DTI-based in vivo results were in accordance with the definition of the post-mortem neuropathological stages ( Brettschneider et al, 2013 ; Braak et al, 2017 ).…”
Section: In Vivo Transfer Of the Staging Conceptsupporting
confidence: 77%
“…A defining trait of ALS is the progression of motor dysfunction. Although disease onset is typically focal, symptoms rapidly spread in a manner that reflects the organization of the underlying neuronal circuitry, usually in a corticofugal fashion [ 3 , 4 ]. Although ALS-causing mutations affect genes, such as FUS, that are ubiquitously and constitutively expressed, MNs appear to be particularly vulnerable.…”
Section: Resultsmentioning
confidence: 99%
“…A specific classification of MND patients is a challenge of growing importance in the light of the continuous efforts of clinical trials with the option that the therapeutic portfolio for ALS might expand, also reflected in the initiative to revise the diagnostic criteria ( Ludolph et al, 2015 ). The diagnostic proof as definite ALS in a given patient with a PLS phenotype might be provided ex vivo by the neuropathological demonstration of cerebral TDP43 pathology according to the neuropathological staging concept of ALS by Braak et al (2013) , Brettschneider et al (2013) , and Braak et al (2017) . In order to assess this neuropathological pattern in MND patients in vivo by magnetic resonance imaging, the hypothesis-guided tract-of-interest-based diffusion tensor imaging technique of the brain has been established ( Kassubek et al, 2014 ; Müller et al, 2016 ; Kassubek et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%